THE IMPLEMENTATION OF HIGHER ORDER THINKING SKILLS (HOTS) ON STUDENTS’ READING COMPREHENSION AT SMA NEGERI 18 MAKASSAR - Desi Mutiara Natalini Allo; Hj. St. Haliah Batau; Ulfah Syam (THE ACADEMIC: ENGLISH LANGUAGE LEARNING JOURNAL, 2022)
This study aimed to know the implementation of higher order thinking skills on students’ reading comprehension at SMA Negeri 18 Makassar. This research focused on pre-experimental research with one group pre-test post-test. The population of this research was class XI students of SMA Negeri 18 Makassar in the academic year 2021/2022. Purposive sampling techniques were used to took one class as the research sample, totaling 26 students. The data was obtained in the form of multiple choices of the reading test. After analyzing data, the writer concluded that the implementation of HOTS in reading comprehension can improve students’ reading comprehension. This evidenced by the average score of students during the pre-test and post-test. The mean score of the students in the pre-test (before the action) was 36.53 and the post-test (after the action) was 68.07. These data indicated that there is a significant difference between the pre-test and post-test. Based on the data from the analysis, it can be concluded that the implementation of higher-order thinking skills can improve students' reading comprehension in class XI Social 4 SMA Negeri 18 Makassar.